2007
DOI: 10.1080/02643290701211928
|View full text |Cite
|
Sign up to set email alerts
|

Processing of syntactically complex sentences relies on verbal short-term memory: Evidence from a short-term memory patient

Abstract: The role of the phonological loop in auditory sentence comprehension was examined in a 35-year-old woman with a selective deficit of verbal short-term memory (STM). More specifically, the objective of the experiment was to test whether sentence comprehension is limited by number of propositions, as suggested by Rochon, Waters, and Caplan (2000), or whether it depends on syntactic complexity. In an offline task, severe impairment was present on cleft objects and centre-embedded structures; the deficit on object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 56 publications
3
28
0
1
Order By: Relevance
“…The finding of an association between STM and sentence comprehension is in line with a number of studies from participants with brain damage, including both case studies (e.g., R. Martin et al, 1994; Papagno et al, 2007) and group studies (e.g., Caplan et al, 2013). A recent study of 61 participants with chronic aphasia by Caplan and colleagues (2013), for example, found that both STM and WM were related to a number of sentence comprehension abilities.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The finding of an association between STM and sentence comprehension is in line with a number of studies from participants with brain damage, including both case studies (e.g., R. Martin et al, 1994; Papagno et al, 2007) and group studies (e.g., Caplan et al, 2013). A recent study of 61 participants with chronic aphasia by Caplan and colleagues (2013), for example, found that both STM and WM were related to a number of sentence comprehension abilities.…”
Section: Discussionsupporting
confidence: 86%
“…Martin & Romani, 1994; R. Martin et al, 1994; Papagno, Cecchetto, Reati, & Bello, 2007; Vallar & Baddeley, 1984; cf. Butterworth, Campbell, & Howard, 1986).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Under conditions of mismatch, syntactic and semantic processing may be more tightly intertwined to allow for sentence reconstruction. This feature of the ELU model may explain why the role of WM in the sentence processing level of speech understanding has not been consistently demonstrated: some results appear to show a heavy dependence on the (explicit) phonological loop functions of WM in sentence comprehension (Papagno et al, 2007), whereas others show that syntactically challenging sentences can be processed online without taxing WM (Waters & Caplan, 2005). Nevertheless, at a neural level there seems to be agreement regarding a specialized region for syntactic processing in the pars opercularis in the inferior frontal gyrus.…”
Section: Current Elu Modelmentioning
confidence: 97%